REFORMULATION OF VILLAGE FUND REGULATIONS AND ALLOCATION BY INTEGRATING GOOD GOVERNANCE AND LAW ENFORCEMENT PRINCIPLES TO ACHIEVE TRANSPARENT MANAGEMENT - Syarif Dahlan; Suhariningsih; Budi Santoso; Muh Fadli (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Numerous villages, up to now, have not implemented Village Fund Regulation (DD)/Village Fund Allocation (ADD) well, especially those villages located distant from the city. However, several villages have succeeded in their development using DD/ADD programs. The basic cause for the villages’ failure in development is the lack of transparency in management due to lenient and unclear regulations on transparency. The current research is an empirical legal study with socio-legal, hermeneutic, and responsive progressive approaches. Data used include primary and secondary data. The primary data are collected through in-depth interviews and questionnaires. The data analysis employs a qualitative juridical technique. The research examines the unachievable equity, the non-existence of legal certainty, and the lack of legal expediency in the transparent management of DD/ADD. Conclusions can be drawn: 1. the formulation of DD/ADD management regulations applied still allows limited transparency and the occurrence of numerous fraud. 2. Reformulation of regulations by integrating transparency and law enforcement principles that instigate new regulations that clearly, strictly, and logically regulate equitable transparency, transparency with legal certainty, and transparency with legal expediency.